Beyond the new public management changing ideas and practices in governance - Minogue, Martin; Polidano, Charles 1967-; Hulme, David (E. Elgar, 1998)
This text brings together a number of specialists who examine the range of ideas and concepts of the new models of reform, paying particular attention to the "new public management" model and to strategies of good governance. It evaluates progress made by governments and aid donors in putting these ideas into practice. Using case studies from both the developed and developing world, it emphasizes the extent to which public management and governance reforms are being applied throughout the international arena. The examples used focus on the problems of policy and institutional transfers between the industrialized world and developing countries. Multidisciplinary in its approach, it draws on literature and research from management studies, political science, sociology, economics and devolopment studies, and points to issues likely to dominate research agenda.